Incomes policy and regulation of wages - Almaz, Oksana; Bozhok, Natalia (My University, 2014)
In a market economy the state has a number of functions, one of which is to ensure fairness among tasks of economic policy - to achieve an equitable distribution of income and economic justice. State regulation of incomes - a very important area of social and economic policy, it should cover all segments of the population, to promote the growth of its real income.
Keywords: income; wages; policy; дохід; заробітна плата; політика; доход; заработная плата; политика; кафедра ділової іноземної мови та міжнародної комунікації